Implementation of SWOT Analysis to Improve Educational Quality at Elementary School 13 Pasaman, West Pasaman Regency - Yuharnis, Yuharnis; Erni, Yusnizar (International Journal of Educational Dynamics, 2024)
This study aims to describe the implementation of SWOT analysis in improving the quality of education at Elementary School 13 Pasaman, identify supporting and inhibiting factors, and develop strategies for quality improvement. A descriptive qualitative method with a case study design was employed, utilizing observation, interviews, and documentation for data collection. The data were analyzed using triangulation. The SWOT analysis revealed several key findings: 1) strengths include the school’s strategic location, well-maintained facilities and infrastructure, qualified teaching staff, a conducive school climate, and coordinated assessment standards involving parents; 2) weaknesses stem from limited parental involvement in the school environment; 3) opportunities include strong parental support for academic and non-academic needs, student achievements in competitions, and harmonious relations with the surrounding community; and 4) challenges involve critical attitudes from student guardians requiring teachers to make thoughtful decisions. Supporting factors for SWOT implementation include proactive stakeholders, such as engaged staff and a progressive principal who promotes strategic planning and development. Inhibiting factors include insufficient community support and understanding of school management. Strategies for quality improvement involve enhancing Koran recitation programs, strengthening character education, expanding extracurricular activities, creating unique school programs, and improving student counseling services.